Effect of Shape on Physico-Chemical Properties of Metronidazole Tablet - Nisar,Huma (2022)
Abstract This work was aimed to analyze metronidazole tablet for its properties by explaining the role of compaction and compression related to its process of manufacturing in round and oblong shape tablets. The desirable features of a tablet that includes a known value of hardness, friability, disintegration, weight variation and dissolution was carefully evaluated. The weight variation test performed on different days for round and oblong shape tablets. All tablets of round shape were within limits of +/- 5% (USP, BP) however some of oblong shape tablets deviating from +/-5% limit. The hardness and friability tests indicate that oblong shape tablets are more prone to breaking during handling and transportation while round shape tablets are well within limits of hardness and friability tests i.e. within 1% and 0.8% (USP, BP). The disintegration time of both round and oblong shape tablets are nearly same and within the limits. The dissolution profile of both round and oblong shape tablets were determined according to USP. The obtained dissolution profile of both shaped tablets were evaluated and compared using two different statistical methods, the fit factor (f1 and f2) and the dissolution efficiency (DE) model. The values obtained were 9 and 64 for f1 and f2 respectively. The DE was found to be 63 and 72 for round and oblong shape. The experimental findings showed that change in shape of tablet affect different physicochemical parameters. In addition, tablet shape enhances tablets mechanical properties, packaging, handling ease and the aesthetic appearance of the tablet.